Comparative Study of Atmosphere Effect on Wood Torrefaction - Rafael Lopes Quirino; Larissa Richa; Anelie Petrissans; Priscila Rios Teixeira; George Durrell; Allen Hulette; Baptiste Colin; Mathieu Petrissans (Fibers, 2023)
Climate change, biomass utilization, and bioenergy recovery are among the biggest current global concerns. Wood is considered an environmentally benign material. Nevertheless, it must be processed for desired applications. Upon thermal treatment ranging from 180 °C to 280 °C, under low oxygen concentrations, wood becomes a material with improved dimensional stability, resistance to fungal attacks, grindability, hydrophobicity, and storage stability. Several strategies for wood treatment have been investigated over the course of the past decades, including the use of steam, nitrogen, smoke, vacuum, water, and hot oil. The goal of this work is to investigate the influence of pressure and atmosphere on the torrefaction of poplar. Through a systematic analysis of poplar wood samples treated under reduced pressures and different atmospheres, while keeping the same heating profile, it was possible to establish that changes observed for mass loss, color change, wood composition (via TGA/DTG analysis), functional groups (via FTIR), elemental analysis, and X-ray diffractograms relate directly to known reaction pathways occurring during torrefaction. Changes observed under reduced pressures have been associated with the relative concentration of oxygen in the reaction atmosphere and to the reduced diffusion times experienced by reactive by-products during the treatment. Conversely, extended diffusion times resulted in more significant changes for reactions carried out under N2, water vapor, and air.